Analisis dan Perancangan Sistem Personalisasi dan Monitoring SLA (Service Level Agreement) Berbasiskan NFC (Near Field Communication) Studi Kasus Akses Kontrol Vendor ke Perangkat Bts (Base Transceiver Station) - Nofita Rismawati; muhamad femy mulya (LPPM, 2018)
NFC (Near Field Communication) is one of the communication technologies between the latest gadgets that use RFID (Radio Frequency Identification) systems to exchange data at close range, about 4 inches. NFC (Near Field Communication) technology, is the principle of standard wireless communication that allows two devices to exchange data when in a position close to one another. The purpose of this research is to analyze and design a personalization system for vendors by utilizing NFC (Near Field Communication) technology that can facilitate vendors to access the doors of BTS (Base Tranceiver Station) devices and at the same time help telecommunications operators in monitoring SLAs (Service Level Agreement) for every vendor who does troubleshooting directly to a BTS (Base Tranceiver Station) device, so that vendor performance can be monitored. In addition, it also helps interested parties (in this case, the telecommunications operator management) in evaluating the performance of a vendor. Key words: NFC, BTS, SLA